التأثيرات المحلية في طابع أبنية مدارس العصور الإسلامية في سورية - نتيفة رولا; منون محمد; طريفي دلال (Latakia University Journal -Engineering Sciences Series, 2014)
إن ملامح الطابع المعماري للمدارس في العصور الإسلامية هي حصيلة تأثير عوامل عديدة نذكر منها: أولاًـــ العوامل الثقافية: كالتأثر بالحضارات السابقة للإسلام كالساسانية في العراق والبيزنطية والهلنستية في سورية ثانياًـــ العوامل البيئية: ونقصد هنا المناخ ومواد بناء التي أثرت في التكوينات السائدة، فعلى سبيل المثال سادت الباحات المسقوفة في المناطق الباردة في حين استخدمت الباحة المكشوفة في المناطق المعتدلة والصحراوية. بينما أثَر توفر مواد بناء محلية في تبني نمط بناء معين ففي الوقت الذي نجد فيه شيوع العمارة الطينية في العراق، نجد ازدهار العمارة بالحجارة في كل من مصر وسوريا. ثالثاً العوامل السياسية التي لعبت ايضا دورا في تشكيل ملامح طابع المدارس حيث كان للحكام تأثير واضح في العمارة فمصر في العصر الطولوني تأثرت بالعمارة العراقية لأن أحمد بن طولون الحاكم كان ذا أصل عراقي. إلا أن هناك عوامل أخرى ساهمت في اختلاف عمارة المدارس من فترة زمنية لأخرى، كما اختلفت من بلد إلى آخر فالعمارة في مصر تختلف عن معاصرتها في سوريا، حتى أنها تختلف في البلد الواحد بين المدن فالعمارة في حلب ليست كالعمارة في دمشق، وهذا يدفعنا للتساؤل حول أهمية المؤثرات المحلية في تصميم المدارس القديمة في العصور الإسلامية. في هذه المقالة سنمر بدايةً على تطور نشوء المدارس الإسلامية عبر التاريخ، ثم سنسلط الضوء على التأثيرات المحلية للمكان كالمناخ ومواد البناء المحلية وكذلك على العوامل المؤثرة على الطابع المعماري عموماً، وصولاً إلى دراسة طابع الأبنية المدرسية في العصور الإسلامية ووضع اليد على أكثر العوامل تأثيراً والتي تطبع الأبنية المدرسية عبر العصور الإسلامية المختلفة. The architectural character of the schools in the Islamic Ages influenced by many factors including: first cultural factors, civilizations pre-Islamic: Sassanian in Iraq, Byzantine and Hellenistic in Syria. Secondly environmental factors, we mean here the climate and building materials that have affected the formations prevailing, for example covered patios prevailed in cold regions, while the open patios used in temperate and desert regions. While the availability of local building materials serve to in the adoption of a particular style building: at a time we find the prevalence of clay or earth architecture in Iraq, Stone Architecture diffused in both Egypt and Syria. Thirdly, the political factors that also play a role in shaping the schools character, where the rules effected on the architecture. So Egypt in Tulunid was affected by Iraqi architecture due to Ahmad Ibn Tulun who was the ruler from Iraqi origin. However, there were other factors which contributed to create the difference between schools building at the same time; The architecture in Egypt differ from its contemporary in Syria even it was different in the same place among cities, the architecture in Aleppo didn’t like the ones in Damascus. So we wonder about the importance of the local effects on designing early schools during the Islamic era. In this paper, we will recite the evolution of Islamic school throughout history, then we’ll focus on the local effects of the place such as the climate and regional building material, as well as the effective factors on the architecture characters generally, finally, we will study the character of school building in Islamic eras in order to find the most powerful factors that are affected on building schools throughout various Islamic eras.